2011
DOI: 10.1021/ic201158v
|View full text |Cite
|
Sign up to set email alerts
|

Novel Cyclopalladated Imino-thiophenes: Synthesis and Reactivity Toward Alkynes and Carbon Monoxide

Abstract: ortho-palladated complexes based on thiophene and benzothiophene ligands 1a and 1b have been synthesized by direct C–H activation under mild conditions. These species were fully characterized, including single-crystal X-ray diffraction analysis. The reactions of these novel complexes with internal alkynes afforded a variety of thieno[3,2-c]pyridinium salts substituted at the 6- and 7-positions. The thiophene-based complex 2a also reacts with carbon monoxide, in the presence of different alcohols, forming the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 100 publications
0
9
0
Order By: Relevance
“…Cyclometallated complexes are of continuing interest due to the possibility of their diverse applications in industrial and medical technologies. [1][2][3][4][5][6][7][8][9][10] In this regard, platinum complexes have been extensively investigated and indicated to have medicinal applications due to their cytotoxicity and luminescence properties. [11][12][13][14][15][16][17][18][19][20][21] We have recently reported some new C,N donor cycloplatinated(II) complexes with bisphosphine ligands, such as dppm = bis(diphenylphosphino)methane or dppa = bis(diphenylphosphino)amine, and indicated that they have significant capabilities of being further investigated as anticancer drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Cyclometallated complexes are of continuing interest due to the possibility of their diverse applications in industrial and medical technologies. [1][2][3][4][5][6][7][8][9][10] In this regard, platinum complexes have been extensively investigated and indicated to have medicinal applications due to their cytotoxicity and luminescence properties. [11][12][13][14][15][16][17][18][19][20][21] We have recently reported some new C,N donor cycloplatinated(II) complexes with bisphosphine ligands, such as dppm = bis(diphenylphosphino)methane or dppa = bis(diphenylphosphino)amine, and indicated that they have significant capabilities of being further investigated as anticancer drugs.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned in the Introduction, no palladacycles derived from a primary arylalkylamine containing either the benzofuran or the benzothiophene ring have been described previously. Moreover, there are only two precedents of similar C , N -palladacycles with the metal at the C3 position of the benzothiophene ring, and in both cases, the nitrogen atom belongs to an imine fragment. , …”
Section: Resultsmentioning
confidence: 99%
“…These examples included: (1) For the benzofuran nucleus: (1a) C , N -, C , S -, , or C , Se -five-membered palladacycles metalated at the C3 position; and (1b) C , N -six-membered palladacycles metalated at C3 . (2) For the benzothiophene nucleus: (2a) C , N -five-membered palladacycles metalated at C3, where the nitrogen atom belongs to an imine or a pyridine moiety, (2b) S , C , N -pincer derivatives containing two five-membered rings, and (3b) C , N -five- or six-membered palladacycles metalated at the C2 position, being the nitrogen part of an imine fragment. , …”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, only a limited number of mono(imino)pyrrole compounds have been reported in the literature (Dawson et al, 2000;Anderson et al, 2006;Carabineiro et al, 2007;Pé rez-Puente et al, 2008). The case is similar for mono(imino)thiophene compounds (Cuesta et al, 2011), in which most of the side arms of the heterocyclic rings were H atoms. To simulate the original structure of a bis(imino)pyridine ligand, we chose to replace an H atom with a methyl group and thus prepare new heterocyclic imino compounds.…”
Section: Introductionmentioning
confidence: 84%